Learning the Simple Past Tense in Narrative Texts: A Study of the Difficulties Experienced by Year 11 High School Students - Andi Endah Pratiwi; Chairil Anwar Korompot; Muh. Tahir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This research was conducted to investigate the difficulties experienced by year 11 high school students at SMA Negeri 3 Makassar. The purpose of this study was to describe the difficulties faced by the students in learning the simple past tense in narrative text, the factors that cause the students' difficulties, and students' and teachers' efforts in solving the issues. This research used a descriptive qualitative approach in the form of a case study. The subject of this study was the 11-year social science students, including five males and four females. In this study, data was gathered through interviews and class observations. The results of this study indicate that there are four difficulties faced by the students in learning the simple past tense through the narrative text, such as difficulties in memorizing irregular verbs, having a lack of vocabulary, do not comprehend the teacher's directions, and students are still unsure about how to utilize the present and past tense. These difficulties are caused by several factors, internal and external factors. The internal factors are mind block, interest, lack of motivation, and anxiety while the external factors are game addiction, family, social environment, and facility. All the challenges and their underlying causes may be resolved with the students' intention and efforts.